Analysis of the Vibration Characteristics of a Boring Bar with a Variable Stiffness Dynamic Vibration Absorber. (1st August 2019) - Li, Lie; Sun, Beibei; Hua, Haitao
Abstract : Boring bars are widely used in deep hole machining. Due to the low stiffness of the long cantilever boring bar, vibration often occurs in the boring process. Vibration suppression can permit higher productivity and a better surface finish. To improve the performance of boring operations, a variable stiffness dynamic vibration absorber (DVA) is added inside the boring bar to reduce the vibration. The stiffness of the DVA is provided by two rubber bushes placed inside the DVA. By changing the axial compression, the stiffness of the DVA can be adjusted to accommodate different excitation frequencies. By establishing the relationship between the stiffness of the DVA and the axial compression of the rubber bush, the optimal stiffness for different excitation frequencies can always be found. A boring experiment is conducted, and the results show that, by selecting a reasonable axial compression, the vibration of the boring bar can be effectively suppressed.